Hierarchical principles of models formation and modelling of electric power systems modes - Kyrylenko, О.; Prihno, V.; Rybina, О. (Видавництво Львівської політехніки, 2010)
The description of construction of a double-lever programm control complex is given. New approaches to a complex problem solving of a state estimation and optimisation of regimes in the conditions of incompleteness and low accuracy of the arriving information are shown.
Keywords: hierarchical control complex; state evaluation; optimization mode; power pool